2017
DOI: 10.17533/udea.iee.v35n1a02
|View full text |Cite
|
Sign up to set email alerts
|

Care models for people with chronic diseases: integrative review

Abstract: Article linked to the research: Predictive factors for complications and nursing care management actions in hypertensive people in primary careFundings: The article is part of a project that received funding from the National Council for Scientific and Technological Development and the Araucária Paraná Foundation. Conflicts of interest: none.Receipt date: February 12, 2016. Resultados. La muestra estuvo constituida por 17 artículos sobre el tema de interés. Del análisis emergieron tres categorías: los costos d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Another benefit of case management observed in the speeches was the fact that the patients feel more informed and, with this, feel more responsible for their recovery and care process. In this regard, a bibliographic review identified the importance of the case manager being a professional nurse, as they are the main reference for the patients and their families, mainly when it comes to health education to promote healthy habits and prevent diseases or complications (28) .…”
Section: Discussionmentioning
confidence: 99%
“…Another benefit of case management observed in the speeches was the fact that the patients feel more informed and, with this, feel more responsible for their recovery and care process. In this regard, a bibliographic review identified the importance of the case manager being a professional nurse, as they are the main reference for the patients and their families, mainly when it comes to health education to promote healthy habits and prevent diseases or complications (28) .…”
Section: Discussionmentioning
confidence: 99%
“…Efficiency is a quality aim in 20 of the scientific articles [26,28,30,32,39,[43][44][45][46][47][48][49][51][52][54][55]57,61,62,65] and in 9 of the grey literature [3,4,12,[14][15][68][69][70]72]. This aim is about using appropriate (amounts of) resources and avoiding waste, including waste of equipment, supplies, ideas, and energy [12].…”
Section: Specifying Aims For Good Quality Chronic Carementioning
confidence: 99%
“…Person-centredness is defined by WHO [70] as the approach to care that consciously adopts the perspectives of individuals, carers, families and communities as participants in, and beneficiaries of, trusted health systems organized around the comprehensive needs of Version 3.0 people rather than individual diseases, and respects social preferences. This is a central dimension in 36 of the scientific papers [18,20,29,[31][32][33][34][35][36][37][38][39][41][42][43][44][48][49][50][51][52][53]58,[62][63][64][65] and ranges from outright mentions of patient-/person-centredness to implicit indications that relate to collaborating with and engaging PwCC in their care and self-management. It is also included in 19 more grey literature [3][4]12,[14][15]68,71,[73][74][75][76][77][80][81][82][83][84]…”
Section: Specifying Aims For Good Quality Chronic Carementioning
confidence: 99%